1988
DOI: 10.1017/s000335610003703x
|View full text |Cite
|
Sign up to set email alerts
|

A study on consistency of differences between cows in rumen outflow rate of fibrous particles and other substrates and consequences for digestibility and intake of roughages

Abstract: In 22 cows given complete diets of 500 g straw and 500 g concentrates per kg fresh weight the outflow rate of small fibrous particles was determined on two occasions to investigate the consistency of this measurement and its association with apparent digestibility. The correlation between the outflow rates on the two occasions werer= +0·90 and the correlation with apparent digestibility wasr= −0·80.In a second experiment, the outflow rates of long and small particles were determined together with rumen retenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 7 publications
0
14
1
Order By: Relevance
“…Particle retention time in ruminants is known to be a heritable trait (Orskov et al 1988;Smuts et al 1995) and may explain at least some of the CH 4 yield variation observed in sheep (Pinares-Patiño et al 2003). Recently, CH 4 yield in sheep in Australia has been directly correlated with the retention time of feed particles and liquid and with the total amount of feed particles and rumen volume (Goopy et al 2013), further supporting this view.…”
Section: Discussionmentioning
confidence: 89%
“…Particle retention time in ruminants is known to be a heritable trait (Orskov et al 1988;Smuts et al 1995) and may explain at least some of the CH 4 yield variation observed in sheep (Pinares-Patiño et al 2003). Recently, CH 4 yield in sheep in Australia has been directly correlated with the retention time of feed particles and liquid and with the total amount of feed particles and rumen volume (Goopy et al 2013), further supporting this view.…”
Section: Discussionmentioning
confidence: 89%
“…DM disappearance values were the greatest at terminal incubation hours across plant species. Many authors (Orskov et al, 1988;Kabuga and Darko, 1993;Tesema et al, 2003;Lanyasunya et al, 2006;Vranic et al, 2009, andLebopa et al, 2011) confirmed the increasing trends of that ruminal degradation of DM as advances in incubation hours. The other possible reason could be condensed tannin concentration of the feed materials.…”
Section: In Sacco Ruminal Dry Matter Disappearancesmentioning
confidence: 91%
“…Pinares-Patiño et al (2003a) reported that the rate of outflow of rumen digesta (FOR) was the most important factor involved in the variation of CH 4 emissions between animals when sheep were fed alfalfa hay and a similar effect appeared to occur in this study. Studies under controlled conditions, both with cattle (Hartnell and Satter 1979;Ørskov et al 1988) and with sheep (Hodgson and Thomas 1975;Faichney 1993), have shown consistent between-animal differences in FOR. If the relationship between CH 4 emission and FOR is confirmed in the longer term and FOR is under genetic control, it raises the possibility of selecting ruminants for reduced methane emission (Gibbs et al 1989).…”
Section: Digestibility Coefficient (%)mentioning
confidence: 93%